Cell-specific copper dyshomeostasis mechanism in Alzheimer’s disease - Michael Okafor; Peter Faller; Nicolas Vitale (Translational Neurodegeneration)
Abstract Alzheimer's disease (AD) is a complex neurodegenerative disorder characterized by progressive decline of cognitive functions, yet its underlying aetiology remains elusive. While amyloid-β (Aβ) and tau pathologies have been extensively studied, emerging evidence suggests that metal and especially copper dyshomeostasis may also play a crucial role in the pathogenesis of AD. This review explores the intricate relationship between copper and AD, shedding light on the multifaceted mechanisms through which copper dysregulation contributes to neurodegeneration. We delve into the impact of copper ions on Aβ aggregation, tau phosphorylation, and oxidative stress, providing a comprehensive overview of the molecular pathways involved. Furthermore, we discuss the interplay between different brain cell types and the impact Cu dysregulation may have on them. The therapeutic implications of targeting copper dysregulation for AD treatment are also addressed, emphasizing the potential of copper-modulating agents in ameliorating cognitive decline. In summary, this review discusses copper dyshomeostasis as a central player in the intricate tapestry of AD pathology, offering new insights and avenues for therapeutic interventions.